Acute Toxicity Test Against Mice (Mus Musculus) On The Lempuyang Gajah Extract (Zingiber Zerumbet (L.) Roscoe Ex Sm.) With Sgot Sgpt Parameters: Uji Toksisitas Akut Terhadap Mencit (Mus Musculus) Pada Ekstrak Lempuyang Gajah (Zingiber Zerumbet (L.) Roscoe Ex Sm.) Dengan Parameter SGOT SGPT - Sofi Rahayu, Bella; Rohmah, Jamilatur; Rini, Chylen Setiyo; Puspitasari (Universitas Muhammadiyah Sidoarjo, 2024)
Lempuyang Gajah (Zingiber zerumbet (L.) Roscoe ex Sm) is a medicinal plant that has many benefits in the medicinal industry. Useful as a tonic, external medicine, anti-seizure and appetite enhancer. This study aims to determine the toxicity of the lempuyang gajah. This research uses laboratory experimental methods. The lempuyang gajah plant was obtained in the village of Terungkulon, Krian. The initial stage was the administration of lempuyang gajah extract with various doses of 4000, 5000 and 6000 mg/kg BB orally, consisting of 5 treatment groups. Parameters observed, changes in toxic symptoms, macroscopic examination and parameters of SGOT, SGPT. The results were analyzed using the One Way ANOVA test. The results of the study after giving the extract did not cause death so it was included in the non-toxic category, there were several symptoms such as weakness and seizures. The levels of SGOT, SGPT showed normal average results, statistically there was no effect (p > 0.05). Macroscopic results showed no changes or abnormalities in the liver. So that the ethanol extract of lempuyang gajah can be said to be safe for humans.